BALANCED SCORECARD AND ITS ROLE IN EVALUATING STRATEGIC PERFORMANCE IN LIGHT OF THE APPLICATION OF PROGRAM AND PERFORMANCE BUDGETING (APPLIED STUDY) - Faris Abdulzahra Abdulhussin Alkhalidy (Scholars Digest Publishing, 2024)
Even the non-national nationalism exists or is capable of showing a complete picture of the distinguished performance well, which leads to the emergence of the new public, and the most important of which is the loss of the balanced scorecard and its balanced face and distinguished for different goals from the last for planning even in the performance budget directed and the barley control method for several dimensions in the balanced scorecard, in other words, it represents a theoretical reference for a future strategy. For this reason, this study has proven the possibility of applying the balanced scorecard system in many Sudanese economic figures and the latest and most appropriate to each other and known for their efficiency and effectiveness under the system of applying the impact balance as well as other control electronics. One of the most important results that I connected to is that the balanced scorecard is one of the advanced methods of examining performance in Sudanese as it depends on a number of dimensions and axes and it is possible to create that the indicators that are used and calculate the tools and then evaluate the performance to reach a result and the most important thing that the study reached is to perform the strong performance system with the balanced scorecard.
Keywords: balanced scorecard, good results, basic software.